PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, DAN INVESTMENT OPPORTUNITY SET (IOS) TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODW 2020-2022 - Gede Upadana Mahendra Wiyasa; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Capital structure is very important for a company because it involves the policy of using the most profitable sources of funds. A good capital structure will have an impact on the company, and indirectly, the company's financial position will increase and the company value will be high. Companies that have an optimal capital structure will produce an optimal level of development, and vice versa. This research aims to explain the influence of profitability, asset structure, and investment opportunity set on the capital structure of food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study was 25 companies determined using the purposive sampling method. The analytical tool used to test the hypothesis in this research uses a multiple linear regression model using the SPSS 25 program. The results of this research show that profitability has a negative and significant effect on capital structure, while asset structure and investment opportunity set have a positive and significant effect on capital structure. Suggestions for further research could be to develop this research by adding other variables such as liquidity variables, sale growth and company size.